Coupled static and dynamic tensile property of granite. Issue 4 (October 2020) - Man, Ke; Liu, Xiaoli
Abstract: The principle of coupled static and dynamic loading is illuminated according to the basic principle of the SHPB, i.e., one-dimensional stress wave propagation and uniformity of the specimen. In the Tianhu area of Xinjiang Province, which is a preselected area for high-level radioactive waste geological disposal, a series of coupled static and dynamic loading was conducted in a borehole. The dynamic tensile strength could reach a maximum level when the axial tensile stress is about 50% of the static tensile strength. Meanwhile, as the axial tensile stress increases, the coupled static and dynamic tensile strength increases obviously, reaching about three times the static tensile stress and about 1.5 times the dynamic tensile strength. The failure model of the coupled test is a tensile failure pattern, which is the same as in the static tension and conventional dynamic loading test. Furthermore, through a series of coupled static and dynamic loadings, the strength of the rock specimen could be obtained under different kinds of axial tensile stress and dynamic loading. Thus, the critical value of the dynamic loading could be confirmed, which is useful for blasting excavation in deep geoengineering.